2017
DOI: 10.1007/s12594-017-0555-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride and Heavy Metal Accumulation by Vegetation in the Fluoride Affected Area of Talupula, Anantapur District, Andhra Pradesh

Abstract: A detailed survey showed that groundwater fluoride was 6.1ppm in the Talupula area of the Anantapur district in southern India which is higher than is normally observed in groundwater elsewhere in India but not so extreme as that reported in Andhra Pradesh (up to 21 mg L−1). Groundwater is used for irrigating agricultural crops as well as for drinking which may expose its population to higher concentrations of fluoride through their diet. A preliminary study examined the concentrations of fluoride in five agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…In general, there are only a few studies regarding fluoride partitioning into different plant parts and even less for the species investigated in the present study. Nagaraju et al 72 detected higher fluoride concentration in bean stems compared to that observed in the present work, despite a lower fluoride concentration in soil, hence the BCF calculated on the basis of this data would be greater than the values obtained in the current study for beans. Fluoride concentration in roots and grains were not reported by Nagaraju et al 72 hence it was not possible to compare our results with TF values from this study.…”
Section: Discussioncontrasting
confidence: 83%
“…In general, there are only a few studies regarding fluoride partitioning into different plant parts and even less for the species investigated in the present study. Nagaraju et al 72 detected higher fluoride concentration in bean stems compared to that observed in the present work, despite a lower fluoride concentration in soil, hence the BCF calculated on the basis of this data would be greater than the values obtained in the current study for beans. Fluoride concentration in roots and grains were not reported by Nagaraju et al 72 hence it was not possible to compare our results with TF values from this study.…”
Section: Discussioncontrasting
confidence: 83%
“…Fluoride bioaccumulation in various plant parts varies according to the mechanisms by which it is transported from soil solution to roots and then translocated from root to shoot. Fluoride is more soluble in acid soils and primarily accumulates in the leaf [56,57]. According to a related study conducted by Edmunds and Smedley (2013), the fluoride content of the leafy part of vegetables grown in this area is significantly higher than the fluoride content of the fruits and tubers [58].…”
Section: Discussionmentioning
confidence: 99%
“…It is primarily found in the leaf. Fluoride accumulation in excess in vegetables results in visible leaf injury and fruit damage [8,56]. Fluoride enters plants via soil and water and then through passive diffusion to the plant roots.…”
Section: Discussionmentioning
confidence: 99%
“…These participants will be followed over the winter and offered larger container gardens appropriate to their spatial contexts to practice growing more foods at home. The expertise of Aitkenhead-Peterson [37][38][39][40] and Brown [41][42][43][44][45][46] in terms of interaction of water and soil, rainwater use, and the development of urban microclimates will be brought to bear in assessing these residential gardens.…”
Section: Research In the Time Of Covid-19mentioning
confidence: 99%
“…Based on the towergarden project, she is currently working on establishing an urban agriculture certification for undergraduates, an online certification in urban agriculture for entrepreneurs and non-profits through extension, and research comparing soil and soil-less production of food in urban centers. She has published work on irrigation water chemistry, and its effect on soil nutrient status across urban centers in Texas [40] and on soil microbial community composition [38], soil nutrient chemistry for smallholder farms in Ghana [37], and plant uptake of Fluoride and heavy metals in small holder farms in southern India [39].…”
Section: Mechanisms For Bringing Together Intellectually Diverse Researchers and Stakeholdersmentioning
confidence: 99%